Repeated Sprint Ability in Young Basketball Players (Part 2): The Chronic Effects of Multidirection and of One Change of Direction Are Comparable in Terms of Physiological and Performance Responses - Attene, Giuseppe; Nikolaidis, Pantelis T.; Bragazzi, Nicola L.; Dello Iacono, Antonio; Pizzolato, Fabio; Zagatto, Alessandro M.; Dal Pupo, Juliano; Oggianu, Marcello; Migliaccio, Gian M.; Mannucci Pacini, Elena; Padulo, Johnny (Frontiers in Physiology, 2016)
The aim of this study was to examine the effects of a 5-week training program, consisting of repeated 30-m sprints, on two repeated sprint ability (RSA) test formats: one with one change of direction (RSA) and the other with multiple changes of direction (RSM). Thirty-six young male and female basketball players (age 16.1±0.9 yrs), divided into two experimental groups, were tested for RSA, RSM, squat jump, counter-movement jump, and the Yo-Yo Intermittent Recovery-Level-1 (Yo-Yo IR1) test, before and after a 4-week training program and 1 week of tapering. One group performed 30-m sprints with one change of direction (RSA group, RSAG), whereas the other group performed multidirectional 30-m sprints (RSM group, RSMG). Both groups improved in all scores in the post-intervention measurements (P<0.05), except for the fatigue index in the RSM test. However, when comparing the two groups, similar effects were found for almost all parameters of the tests applied, except for RPE in the RSA test, which had a greater decrease in the RSAG (from 8.7 to 5.9) than in the RSMG (from 8.5 to 6.6, P=0.021). We can conclude that repeated 30-m sprints, either with one change of direction or multidirectional, induce similar physiological and performance responses in young basketball players, but have a different psycho-physiological impact.